Straightforward Superbase-Mediated Reductive O-Phosphorylation of Aromatic and Heteroaromatic Ketones with Red Phosphorus in the Superbase Suspension KOH/DMSO(H2O) - Vladimir A. Kuimov; Svetlana F. Malysheva; Natalia A. Belogorlova; Ruslan I. Fattakhov; Alexander I. Albanov; Irina Yu. Bagryanskaya; Nikolay I. Tikhonov; Boris A. Trofimov (Molecules)
It was shown for the first time that diaryl(hetaryl)ketones are capable of directly phosphorylating with red phosphorus in the superbase suspension KOH/DMSO(H2O) at 85 °C for 1.5 h to afford potassium bis(diaryl(hetaryl)methyl)phosphates that were earlier inaccessible in a yield of up to 45%. The ESR data demonstrate that unlike previously published phosphorylation with elemental phosphorus, this new phosphorylation reaction proceeds via a single electron transfer from polyphospide anions to diaryl(hetaryl)ketones. This is the first example of the C-O-P bond generation during the phosphorylation with elemental phosphorus in strongly basic media, which usually provides C-P bond formation.